2014
DOI: 10.1590/0004-2730000003312
|View full text |Cite
|
Sign up to set email alerts
|

Sitting-height measures are related to body mass index and blood pressure levels in children

Abstract: Objective: Sitting height (SH) is an important parameter in the evaluation of children with grow th and pubertal disorders. Besides this, it has been viewed as a biomarker of cardiovascular risk, which is increased in adults with relatively short legs. So, the aim of this study was to evaluate the relationship between body proportions and cardiovascular risk markers in children. Subjects and methods: Eight hundred and seventeen children aged 6-13 years were evaluated. Weight, height, sitting-height (SH), sitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Similar findings were reported among Chinese [9], Brazilian [8] and rural South African [10] children and adolescents. The possible explanation for these findings could be that BP at the heart level must surpass the hydrostatic pressure induced by vertical distance between the heart and the head, to ensure an adequate perfusion of a child's brain [23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings were reported among Chinese [9], Brazilian [8] and rural South African [10] children and adolescents. The possible explanation for these findings could be that BP at the heart level must surpass the hydrostatic pressure induced by vertical distance between the heart and the head, to ensure an adequate perfusion of a child's brain [23].…”
Section: Discussionsupporting
confidence: 87%
“…SH not SH/H was reported to be associated with BP in Brazilian children [8]. Furthermore, Dong et al [9] study exhibited that SH was associated with BP in Chinese children and adolescents.…”
Section: Introductionmentioning
confidence: 94%
“…Yabanci et al (10) reported MUAC to be a predictor of height in the age group 7-10 years, while waist circumference was not a predictor of height for both sexes. Even though sitting height was reported to be a better predictor of total BMI (1,26) , there has been no study showing the correlation between height and sum of four skinfolds.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in SHR found in or between different population groups may be associated with variations in BMI of some 5 kg/m 2 , with weight and composition being kept constant [7]. Some researchers reported a positive association of SHR with BMI and body fat percentage [8,9]. Body shape is also an important determinant of risk status.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%